2016
DOI: 10.1016/j.ophtha.2016.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Latanoprostene Bunod 0.024% versus Timolol Maleate 0.5% in Subjects with Open-Angle Glaucoma or Ocular Hypertension

Abstract: In this phase 3 study, LBN 0.024% qpm demonstrated significantly greater IOP lowering than timolol 0.5% BID throughout the day over 3 months of treatment. Latanoprostene bunod 0.024% was effective and safe in these adults with OAG or OHT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(121 citation statements)
references
References 33 publications
6
109
1
5
Order By: Relevance
“…This radical affects an early step in the replication cycle of influenza viruses and NO has been shown to severely impair the replication of influenza A and B viruses 11. In the outflow physiology, NO has been reported to contribute to the physiological regulation of aqueous humor outflow and to lower intraocular pressure in various animal models and human patients 5, 12, 13, 14, 15…”
Section: Introductionmentioning
confidence: 99%
“…This radical affects an early step in the replication cycle of influenza viruses and NO has been shown to severely impair the replication of influenza A and B viruses 11. In the outflow physiology, NO has been reported to contribute to the physiological regulation of aqueous humor outflow and to lower intraocular pressure in various animal models and human patients 5, 12, 13, 14, 15…”
Section: Introductionmentioning
confidence: 99%
“…This pivotal randomized, controlled, double-masked trial, evaluated the efficacy and safety of LBN (BOL-303259-X) compared to timolol on a large scale and with a noncrossover design for primary end points 68–71. Four hundred and twenty adult subjects with OHTN or OAG, including pseudoexfoliative and pigmentary glaucoma, at multiple centers throughout the USA and EU were randomized 2:1 to receive either LBN 0.024% once daily at 8 PM or timolol maleate 0.5% BID (8 AM and 8 PM) in the study eye for 3 months.…”
Section: Efficacy and Comparative Studiesmentioning
confidence: 99%
“…These results were pooled with data from the APOLLO study; all subjects demonstrated IOP lowering from baseline over this period (see “APOLLO” section) 68–71…”
Section: Efficacy and Comparative Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitric oxide (NO), a key signaling molecule responsible for mediating a wide array of physiological roles across multiple biological systems, decreases outflow resistance and lowers IOP in various animal models and human patients. [513] Due to the therapeutic potential of NO, many efforts have focused on developing NO-donating compounds for glaucoma. In particular, latanoprostene bunod (VESNEO; Bausch and Lomb), a modified version of the existing glaucoma drug latanoprost, contains an NO-donating moiety and is modestly effective at reducing elevated IOP by ≈1.5 mmHg over latanoprost alone in ocular hypertensive patients.…”
mentioning
confidence: 99%